Optimasi Mi Basah Daun Kelor dengan Penambahan Tempe dan Lele sebagai Pangan Padat Gizi: Moringa Leaf Noodle Optimization Enriched with Tempe and Catfish as a Nutrition-Rich Food - Dian Rizqi Novitasari; Bara Yudhistira; Cantika Aurellia Azarine; Putri Wulan Ramadhani; Sechatabina Shahia Majida; Xaviera Angelica Gultom (Jurnal Teknologi dan Mutu Pangan, 2026)
Wet noodles are a high-carbohydrate, flour-based product that is low in minerals and protein. Fortification efforts are carried out to improve nutrition by adding moringa leaves, tempeh flour, and catfish. This study aims to determine the nutritional value of modified wet noodles containing moringa leaves and tempeh flour, as well as catfish, and to identify total calories and the nutritional adequacy index. This study used a one-factor completely randomized design with the following treatments: Mo (2% moringa leaf flour); MoT (2% moringa leaf flour and 10% tempe flour); MoL (2% moringa leaf flour and 5% catfish); MoTL (2% moringa leaf flour, 10% tempe flour, and 5% catfish). The moisture, ash, fat, carbohydrate, and protein contents were then analyzed, and the total calories and the percentage of macronutrient adequacy were calculated. The results showed that the addition of moringa leaves, tempeh flour, and catfish significantly affected the proximate composition of wet noodles (p<0.05). MoTL contained the highest protein (6.99±0.12%) and fat (3.85±0.99%) content, while Mo contained the highest carbohydrate content (37.48±0.16%). Modified wet noodles with moringa leaves, tempeh flour, and catfish can meet 11.66% of the protein, 6.42% of the fat, and 9.31% of the carbohydrates, based on an energy requirement of 2150 kcal per day, in a 100g serving. The conclusion of this study is that the combination of moringa leaves, tempeh flour, and catfish can increase the nutritional content of wet noodles and has the potential to be a nutrient-dense food alternative.